Detection of persistent ductus in hypoplastic left heart syndrome by contrast echocardiography. Issue 5 (November 1980) - Mortera, C; Leon, G
Abstract : A patient with hypoplastic left heart syndrome was studied using contrast echocardiography after peripheral venous injection of dextrose. The combination of the parasternal and suprasternal approach allowed for identification of the right ventricular cavity, excluded the presence of right-to-left intracardiac shunts, and established normal ventriculoarterial connections. From the abdominal approach, the abdominal aorta was identified as an echo-free space corresponding to this structure in position, which became opacified after peripheral injections of dextrose into the left-hand vein. In view of the suprasternal and parasternal findings opacification of the abdominal aorta could only have occurred in the presence of a pulmonary artery to descending aorta shunt through a persistent ductus arteriosus.